Distance Variation Approach in Elementary School Students: Learning Outcomes of Underhand Passing - Nur, Nirmawati; Fahrizal, Fahrizal; Suwardi, Suwardi; Hudain, Muh. Adnan; Adil, Ahmad (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to enhance the learning outcomes of underhand passing in volleyball games by using a distance variation approach specifically designed for fifth-grade students at public elementary schools. The research method employs classroom action research, a one-cycle process that involves stages of planning, action, observation, and reflection. The subjects of the study were 22 fifth-grade students at Public Elementary School Parak No. 11 Kepulauan Selayar. The distance variation approach applied includes distances of 2 meters, 3 meters, and 4 meters with a focus on the assessment of accuracy (0-30), strength (0-30), and technique (0-40). The results of the study showed an increase in underhand passing ability from the initial condition, where 13 students were in the "less" category, 8 students in the "enough" category, and 1 student in the "good" category, to 0 students in the "less" category, 18 students in the "enough" category, and 2 students in the "good" category in cycle I with an average score of 84.59, and all students were declared complete in underhand passing learning outcomes. Based on the results of the study, it can be concluded that the distance variation approach is effective in improving the learning outcomes of underhand passing in volleyball games for fifth-grade students of Public Elementary School, with a completion rate reaching 100%.